2020
DOI: 10.1016/j.chest.2020.08.722
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhage as a Consequence of Microscopic Polyangiitis Due to Covid-19

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a small vessel vasculitis of which microscopic polyangiitis (MPA) is a subset. They are known to cause life threatening renal failure and/or pulmonary hemorrhage. Viruses are a known trigger of vasculitis, including MPA. (1) We present a case of MPA caused by COVID-19 presenting as diffuse alveolar hemorrhage (DAH) CASE PRESENTATION: 55 year old female with a past medical history of hemorrhagic stroke, hypertension & asthma who presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among the 25 cases, we found in the literature (median age of 49 years with 13 females) (Table 2), AAV was diagnosed one to six months after COVID-19 in 12 patients [11,[16][17][18][19][20][21][22][23][24][25][26] while COVID-19 and AAV were diagnosed during the same admission in 11 cases [5,[27][28][29][30][31][32][33][34][35][36]. It is noteworthy that severe AAV with life-threatening alveolar haemorrhage can follow a mild COVID-19 infection, exemplified by two patients who had mild COVID-19 (managed with self-quarantine but not requiring hospital admission) but subsequently died following pulmonary haemorrhage [12,21].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 25 cases, we found in the literature (median age of 49 years with 13 females) (Table 2), AAV was diagnosed one to six months after COVID-19 in 12 patients [11,[16][17][18][19][20][21][22][23][24][25][26] while COVID-19 and AAV were diagnosed during the same admission in 11 cases [5,[27][28][29][30][31][32][33][34][35][36]. It is noteworthy that severe AAV with life-threatening alveolar haemorrhage can follow a mild COVID-19 infection, exemplified by two patients who had mild COVID-19 (managed with self-quarantine but not requiring hospital admission) but subsequently died following pulmonary haemorrhage [12,21].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of COVID-19 in patients with ANCA-associated vasculitis appears to be similar to that of the general population [ 14 ]. There has been another case of a patient with COVID-19-associated microscopic polyangiitis reported as well [ 15 ]. Uppal et al have also reported cases with de novo ANCA vasculitis with glomerulonephritis in patients with COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has also been found to induce and/or exacerbate various other autoimmunological disease processes [2] . Different phenotypes have been reported in the literature, affecting integumentary, renal, and respiratory systems with a variety of clinical manifestations associated with each [5] , [6] , [7] , [18] . However, there have been no reported cases of severe GIH caused by SARS-CoV-2 associated vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…A rare manifestation that carries a high mortality is an involvement of the gastrointestinal (GI) tract [4] . GI involvement can lead to severe life-threatening haemorrhage and often requires prompt surgical management [5] , [6] , [7] . Currently, there are no specific standards of care or guidelines to guide decision making for these patients.…”
Section: Introductionmentioning
confidence: 99%